2017
DOI: 10.1515/hukin-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Training Level Does Not Affect Auditory Perception of The Magnitude of Ball Spin in Table Tennis

Abstract: Identifying the trajectory and spin of the ball with speed and accuracy is critical for good performance in table tennis. The aim of this study was to analyze the ability of table tennis players presenting different levels of training/experience to identify the magnitude of the ball spin from the sound produced when the racket hit the ball. Four types of “forehand” contact sounds were collected in the laboratory, defined as: Fast Spin (spinning ball forward at 140 r/s); Medium Spin (105 r/s); Slow Spin (84 r/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…Thus, adding auditory information to visual signals helped better predicting outcomes in table tennis (Park, Kim, Kwon & Christou, 2016, Wang, Liao, Lundgren Lyckvi & Chen, 2016. Furthermore, auditory information contributes to the identification of ball spins (Santos et al, 2017). These findings are supported by Bischoff et al (2014), who analyzed anticipation of novices to table tennis strokes shown in occluded videos.…”
Section: Introductionmentioning
confidence: 69%
“…Thus, adding auditory information to visual signals helped better predicting outcomes in table tennis (Park, Kim, Kwon & Christou, 2016, Wang, Liao, Lundgren Lyckvi & Chen, 2016. Furthermore, auditory information contributes to the identification of ball spins (Santos et al, 2017). These findings are supported by Bischoff et al (2014), who analyzed anticipation of novices to table tennis strokes shown in occluded videos.…”
Section: Introductionmentioning
confidence: 69%
“…Isto quer dizer que a percepção auditiva poderia ser utilizada para produzir respostas mais rápidas no tênis de mesa. De fato, mesatenistas de alto rendimento parecem utilizar o som do contato da bola com a raquete como indicador para magnitude de rotação (SANTOS et al, 2017), tipo de efeito e até direção da bola (BISCHOFF et al, 2014 (WANG, 1996). A partir de 1970 os chineses (potência mundial na modalidade até os dias de hoje) começaram a estudar sistematicamente os efeitos no tênis de mesa (WANG, 1996).…”
Section: Páginasunclassified
“…Remetendo para o tênis de mesa, apesar de o atleta ter que pensar em vários fatores para ter êxito no ponto como, aonde a bola vai, onde irá jogar, posicionamento do corpo no espaço, qual golpe vai utilizar, ruídos da torcida, a atenção seletiva está fixa no som que será produzido quando a raquete tocar a bola para então, reagir apropriadamente de acordo com o timbre do som da bola. Durante todos esses eventos, o atleta tem que prestar muita atenção no timbre do som que raquete produz quando toca na bola, pois é daí que o atleta saberá se a bola está com muita, média ou pouca rotação(SANTOS et al, 2017). Diferentes intensidades de rotação produzem diferentes timbres sonoros(SANTOS et al, 2017).…”
unclassified
See 2 more Smart Citations